An Analysis of Conversational Maxims in Casual Conversation - Muhammad Aulia Taufiqi; Abdul Hanan; Aulia Priangan (Sekolah Tinggi Agama Islam Ma'had Ali Cirebon, 2021)
This study was aimed to analyze the conversational maxims appeared and flouted by the speakers in casual conversation which are conducted by two students of English Language Education, Graduate Program of State Semarang University. In order to achieve the goal, the writer used descriptive qualitative research design. Therefore, this study is conducted systematically through the technique of data collecting and data analysis. As the results of this research, the writer divided into two categories. The first result, the writer found out that maxim of quality was the most appeared in the conversation, the frequency appeared of maxim of quantity was 16 times, followed by maxim of quality with 13 times appeared, 2 times appeared for the maxim of relation and only 1 time for maxim of manner. The second result showed that there were 3 kinds flouting maxims in the conversation. The flouting maxims that the speakers did were maxim of quantity (only 1 time) and maxim of quality (2 times). From the result, it implicated that the speakers obey the rule of Gricean maxims. It also means that the conversation runs smoothly and both of the speakers understand what they uttered in the conversation. Although there is some flouting inside the conversation, it does not mean that there is some problem occur in the conversation. Keywords: conversational maxims, flouting maxim, casual conversation